THE INFLUENCE OF FINANCIAL DEVELOPMENT ON EMISSIONS IN INDONESIA WITH ECONOMIC GROWTH AS A MODERATING VARIABLE - Muhammad Risal Tawil; Emi Yulia Siska; Muhammad Lucky; Subur Harahap; Melinda Melinda (ITB AAS Indonesia Surakarta, 2024)
Abstract This research aims to examine the influence of financial development on emissions in Indonesia in 2015-2023 by adding economic growth as a moderating variable. The data is panel data, which was tested with the help of SmartPLS software. The research results show that financial development has a significant and positive effect on emissions. Economic growth is able to moderate the relationship between economic growth and emissions disclosure. It is hoped that this research will become a basis for consideration for investors in making investment decisions, especially in companies. Keywords: Economic Growth, Emissions, Financial Development.